Methane Hydrate, A Special Clathrate: Its Attributes and Potential. - Max, M. D.; Pellanbarg, R. E.; Hurdle, B. G. (1997)
Gas hydrates are pressure-stabilized, ice-like compounds found in the cold deep-ocean environment, especially Polar oceans. Natural gas, primarily methane, is held within a water-molecule crystal lattice and thermodynamically stabilizes the structure via hydrogen bonding. Hydrate readily forms in the Hydrate Stability Zone in which hydrate is thermodynamically stable. This region extends downward from the sediment surface at the sea bottom to a depth determined by the local heat flow and water depth, e.g. pressure. Although many publications have recorded the presence of gas hydrate, which commonly stores 160 - 180 volumes of gas (methane, STP) per volume of hydrate, in virtually all of the world's oceans, widespread perception of their extent is unclear because hydrates have been mainly treated as a scientific curiosity or engineering hazard. It is increasingly clear that the unique chemistry of hydrates may allow for new fuel storage and transport applications. This report is intended as a general reference text for non-gas hydrate specialist scientists and for non-scientists with a technical background. p2